Computer-mediated political expression: A conceptual framework of technological affordances and individual tradeoffs. Issue 1 (2nd January 2023) - Neubaum, German; Weeks, Brian
ABSTRACT: Digital media provide individuals platforms to express political views. Despite the significant scholarly attention to how and why political expression occurs through technologies and to what effect, research remains fragmented in its theoretical frameworks. The present work synthesizes research on computer-mediated communication and political communication to offer a framework that describes theoretically (a) which technological affordances lead (b) to which psychological processes with (c) which politically relevant actions. We address these questions in the context of four different technological affordances. In doing so, we emphasize the psychological cost-benefit calculations that occur when deciding whether to engage in political expression online.